Entre o marginal e o laboral: o trabalho de garotos de programa na cidade de Fortaleza/CE - Abreu, Vinício Brígido Santiago (2014)
Prostitution today achieves outstanding academic and social visibility - which differs from acceptance, respect and openness for coexistence - in order to customize many of the discussions on the intersection work-sexuality. I understand prostitution as sex work that performs affective / erotic / sexual acts in various ways, encouraged by exchanges of material and symbolic resources and being set up as a commercial venture for financial gain. The rentboy, male prostitution main character and focus of this study, can be defined as any person who, for remuneration, in the usual way, in any form, indulges in sexual relations with persons of the same sex or opposite sex. Nowadays these sex workers are relegated to marginalization, social exclusion, job insecurity and guilt; having access to health, to Labor Law, Public Safety and to mainly dignity, relegated when associated with their work activities. This activity gives them a situation of intermittent or link apparently weakened in relation to the labor market. These precarious work contracts occur without well-defined collective goals, lacking "description of the subject in carrying structures of meaning" and integrated projects that give meaning to social interactions. Based on this, we aimed to investigate the work of male prostitutes in the city of Fortaleza, understanding the implications and impact of this work on the lives of rentboys, as well as identify and characterize the points of male prostitution and its actors, in particular the work performed in gay saunas; searches negotiations and rules contained in these contexts; examine differences related to local, targeted audience and characteristics of boys; and analyze the processes of affiliation / disaffiliation experienced by insertion / labor and social marginalization of male prostitutes.. We opted for a qualitative research methodology, through ethnographic resources in the insertion and retention of the researcher in the areas of male prostitution in the city and the Sociological Discourse Analysis as a resource for conducting interviews and data analysis. After identifying the areas of prostitution, two gay saunas in Fortaleza as a locus for research were chosen. 10 months of observation were dedicated saunas, 4 interviews were conducted formal and several informal conversations occurred with rentboys. Male prostitution in Fortaleza proved to be an area of conflict, the lack of labor rights and often civilians and comply with the laws. Were featured in the interviews: the symbolic violence at work, the lack of representation of class, visibility of interests and involvement in the development of policies to them. In this marginal space rentboys acts using resources of creativity to stay in the activity. At the same time, this activity is directly linked with the formation of their personal identity, their attitudes towards the world and its self-value judgment.